Development of spatial inspection methods to support building inspections and compliance - Aboshiqah, Saud Eissa (Curtin University, 2014)
The use of spatial information is important to performing building inspections and determining compliance according to regulations. This research identifies the current issues relating to lack of access to spatial information, poor integration of data sources and lack of quality information in the inspection process. A spatially-enabled framework to support building inspections was designed and proposed. A prototype was developed for a case study in a district of Riyadh, Saudi Arabia, and used to evaluate the framework. The prototype utilised a range of data and imagery of various quality to identify and compare instances of violations with calculated certainties. Results indicate substantial benefits to building inspectors for integrating a spatially-enabled process into a building inspection workflow.